Growth diversity, heritability, and genetic correlation of 4-years-old of Alstonia angustiloba progeny test in Wonogiri, Central Java. Issue 1 (November 2021) - Mashudi,; Setiadi, D; Pudjiono, S; Susanto, M; Baskorowati, L; Hendrati, R L; Hidayati, N
Abstract: Alstonia angustiloba is a local tree species that have potential for community forest plantation; therefore, it is important to provide improved seeds. This study aimed to determine the diversity of growth, estimate the value of heritability, and the genetic correlation of the 4-years-old A. angustiloba progeny test. Randomized Completely Block Design with two factors (population and family) were used in this study. In this study, families are nested in the population. The population factors consisted of 4 levels, and family factors consisted of 43 families. The analysis of variance showed that height and stem diameter growth were significantly different between populations and families at four years old. The best height and stem diameter growth at the population level was obtained from the Pendopo population, 4.45 m and 7.71 cm, respectively. At the family level, the best height growth was obtained from 9 families (4.46-5.06 m), and the best stem diameter growth was obtained from 11 families (7.48-8.72 cm). The estimated individual heritability value for height was 0.41, and stem diameter was 0.23. Estimated family heritability values were 0.66 for height and 0.50 for stem diameter. The genetic correlation between height and stem diameter was 0.97.